Global survey of limestone used in poultry diets: calcium content, particle size and solubility - S. Gilani; A. Mereu; W. Li; P.W. Plumstead; R. Angel; G. Wilks; Y. Dersjant-Li (Journal of Applied Animal Nutrition)
Limestone is used in poultry diets as a calcium (Ca) source. Feed formulation is often based on an estimate of limestone Ca content or, less frequently, wet chemistry analysis. However, limestone composition may vary, which has not previously been studied on a large scale. In this study, 641 limestone samples supplied to poultry feed mills in 40 countries across eight global regions were collected and analysed for macro- and micromineral content, particle size (geometric mean diameter, GMD), and in vitro solubility. Mean Ca content of fine limestone (GMD<1000 μm, n=566) was 37.8% (range 33.3-39.7%) and for coarse limestone (GMD>1000 μm, n=75) was 38.0% (range 34.7-40.0%). There was marked variation among and within regions in the concentration of other macro minerals and microminerals. Particle size (GMD) of fine limestone was 288 μm (range 37.7-991.9 μm) and 1,689 mm for coarse limestone (range 301.6-3,067.9 μm). In vitro solubility of fine limestone (5 min incubation, pH=3.0) was 68.4% (range 18.8 to 99.4%). Particle size only explained 52% of the variation in 5 min incubation solubility (R2=0.52). For coarse limestone, mean solubility (30 min incubation) was 65.5% (range 23.2-96%) which was not correlated (R2=0.09) with particle size. Particle size and solubility rate of limestone have been shown to alter Ca and phosphorus utilisation in broilers and laying hens. Hence, better understanding of variation in mineral analysis, particle size and solubility rate would enable more accurate feed inclusion and subsequently digestibility to support health and performance.